The formation of educationaly-informational RESOURCES for people with sight defects. - O. Lozytskyy; O. Pasichnyk (Kherson State University, 2009)
In this article main problems of the people with sight defects education with the help of information technologies is outlined. Technologies and algorithms which are used for DAISY books creation are described in this article. The actual state of providing and development of technologies for blind people is stressed.